catena-Poly[[lead(II)-μ-(2-oxidobenzaldehyde isonicotinoylhydrazonato)] methanol monosolvate] - Gholam Hossein Shahverdizadeh; Seik Weng Ng; Edward R. T. Tiekink; Babak Mirtamizdoust (Acta Crystallographica Section E, 2011)
The Pb atom in the polymeric title compound, {[Pb(C13H9N3O2)]·CH3OH}n, is five-coordinated within an N2O2 donor set and a lone pair of electrons, as the N-isonicotinamidosalicylaldiminate ligand coordinates the PbII atom via the O,N,O′-donors and simultaneously bridges a neighbouring Pb atom via the pyridine N atom; the coordination geometry is based on a trigonal bipyramid with the O atoms in axial positions. The resulting supramolecular chain is a 31 helix along the c axis. These chains are linked via intermolecular Pb...O,N interactions, as well as O—H...O hydrogen bonds.